2009
DOI: 10.1136/bjo.2009.163584
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous spectral domain OCT and fundus autofluorescence imaging of the macula and microperimetric correspondence after successful repair of rhegmatogenous retinal detachment

Abstract: FAF changes may lag behind ultrastructural changes in the OCT, some of which may reverse with the passage of time. The present study demonstrates the ultrastructural changes assessed with simultaneous FAF and sdOCT and their relation with visual outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 26 publications
4
52
0
Order By: Relevance
“…SD-OCT has allowed us to image the foveal microstructural anatomic abnormalities of the outer retina to the extent that we can predict functional recovery with a greater degree of accuracy. Similar to previous reports concerning retinal reattachment, where the integrity of the ELM was identified as a critical parameter for predicting Eye restoration of photoreceptors, 8,9 our findings suggest that combined disruptions of the ELM and IS-OS junction predict worse visual outcomes for MH repair than isolated IS-OS disruptions. The findings of this article complement those of Wakabayashi et al, 15 who, while studying ELM recovery, IS-OS recovery, and visual outcomes following MH repair, found that early postoperative reconstruction of the foveal ELM helps predict restoration of the foveal photoreceptors and better visual outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…SD-OCT has allowed us to image the foveal microstructural anatomic abnormalities of the outer retina to the extent that we can predict functional recovery with a greater degree of accuracy. Similar to previous reports concerning retinal reattachment, where the integrity of the ELM was identified as a critical parameter for predicting Eye restoration of photoreceptors, 8,9 our findings suggest that combined disruptions of the ELM and IS-OS junction predict worse visual outcomes for MH repair than isolated IS-OS disruptions. The findings of this article complement those of Wakabayashi et al, 15 who, while studying ELM recovery, IS-OS recovery, and visual outcomes following MH repair, found that early postoperative reconstruction of the foveal ELM helps predict restoration of the foveal photoreceptors and better visual outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…The integrity of the ELM appears to have a critical role in restoration of the photoreceptor microstructures. 8,9 Several clinicopathological studies of MH repair have suggested that anatomical repair of full-thickness MHs requires proliferation of glial cells, believed to be originated from Mü ller cells. [10][11][12][13] Madreperla et al 11 demonstrated the sealing of a break in the ELM by Mü ller cell processes in an eye with a stage III MH.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The current report used an ultra-wide-field camera that allows a 2001 view of the retina with a single frame. Peripheral views of the retina are valuable in imaging RRDs because this condition is a peripheral disease (ie, results from a retinal break in the periphery that may progress posteriorly).…”
Section: Discussionmentioning
confidence: 99%
“…Spectral-domain optical coherence tomography provided direct visualization of in vivo retinal morphology, allowing high-resolution observation of individual layers of the macula, thereby providing greater information for structural postoperative macular changes. Recent OCT studies have reported disruptions of photoreceptor microstructures and integrity of the outer retinal bands at the fovea in cases of macula-off RRD 5,[17][18][19]32,33 and other retinal diseases (e.g., macular hole 20,34 and central serous chorioretinopathy 35 ). In the present study, SD-OCT facilitated precise measurement of retinal layer thickness and evaluation of outer retinal band integrity.…”
Section: Discussionmentioning
confidence: 99%